Validity of a questionnaire on self-efficacy for Pap test adherence screening - Urrutia, María-Teresa; Padilla, Oslando (Frontiers in Oncology, 2022)
Introduction: Self-efficacy has been related to different health preventive behaviors, included adherence to the Papanicolaou test—also called Pap smear or Pap test. The aim of this study is to test construct and criterion validity and reliability of a questionnaire on self-efficacy and the Pap test in Chilean women. Method: This study was carried out on a sample of 969 women of ages from 25 to 64, who are users of the public health care system in Santiago, Chile. The validity of the Self-Efficacy Scale for the Pap Smear Screening Participation (SES-PSSP) questionnaire was done by confirmatory factor analysis, external criteria by t-test, and reliability by Cronbach’s alpha. Results: Three models were tested, obtaining a questionnaire with 20 items and 2 dimensions. The criteria validity was confirmed by adherence to the Pap test. The final questionnaire has a reliability of 0.95, measured by Cronbach´s alpha. Conclusion: A valid and reliable questionnaire to measure self-efficacy in relation to the Pap test is a relevant contribution in cervical cancer prevention, especially related to interventions focused on increasing adherence.